Bimetallic zeolite imidazolium framework derived multiphase Co/HNC as pH-universal catalysts with efficient oxygen reduction performance for microbial fuel cells. (10th January 2023) - Ding, Fengyue; Liu, Hanjun; Jiang, Xuebin; Jiang, Yu; Cheng, Jingsai; Tu, Yuankun; Xiao, Wei; Li, Chuanhua; Yan, Xuemin
Abstract: Here, the metallic Co encapsulated in hierarchical porous nitrogen-doped carbon (Co/HNC) catalysts is synthesized by pyrolysis of bimetallic (Co, Zn) zeolite imidazolium framework (ZIF) precursors to facilitate oxygen reduction reaction (ORR) in microbial fuel cell (MFC). Importantly, the highly dispersed cobalt nanoparticles are completely encapsulated in the N-doped hierarchical porous carbon, with abundant metal-nitrogen active sites and high degree of graphitization, which is very favorable for the ORR process. As a result, the Co/HNC as pH-universal catalyst shows remarkable ORR properties in alkaline, acidic and neutral environments. More notably, the density functional theory (DFT) calculation demonstrates that the introduction of cobalt can reduce the ORR overpotential and improves the ORR catalytic activity. Furthermore, the assembled MFCs with Co/HNC as cathode catalysts also exhibit high power density of 1324.5 mWm −2, and an output voltage of 0.48 V. Consequently, the investigation provides a new perspective for preparing high-performance and stable electrocatalysts for MFC devices.